PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA PETERNAKAN PASARIBU CHICKEN AIMAS - Dian Agata Sesilia Pasaribu Dian; Sahiruddin Sahiruddin; Dian Nitari Ribanor Sabarudin (LPPM Universitas Abdurrab, 2026)
The goal of this project is to create a web-based sales information system for Pasaribu Chicken Aimas Farm in order to solve issues with manual sales management, making transaction recording less effective. The developed system is expected to support transaction processing, customer data management, product stock management, and sales reporting in a faster, more accurate, and integrated manner. This investigation employed the prototyping approach as its methodology, which consists of the stages of requirements gathering, prototype design, prototype evaluation, system coding, system testing, also implementation. The Black Box Testing approach was used to test the system, which achieved a success rate of 100%, indicating every system feature operates in accordance with user specifications. In addition, the level of system usability was measured using the System Usability Scale (SUS) method and obtained an average score of 83.75, which falls into the Good category. The results indicate that the developed web-based sales information system is capable of improving the effectiveness of sales management at Pasaribu Chicken Aimas Farm and providing convenience for users in conducting transactions and managing data.